Functional Characterization of Preadipocytes Derived from Human Periaortic Adipose Tissue. (25th October 2017) - Vargas, Diana; Camacho, Jaime; Duque, Juan; Carreño, Marisol; Acero, Edward; Pérez, Máximo; Ramirez, Sergio; Umaña, Juan; Obando, Carlos; Guerrero, Albert; Sandoval, Néstor; Rodríguez, Gina; et al.
Abstract : Adipose tissue can affect the metabolic control of the cardiovascular system, and its anatomic location can affect the vascular function differently. In this study, biochemical and phenotypical characteristics of adipose tissue from periaortic fat were evaluated. Periaortic and subcutaneous adipose tissues were obtained from areas surrounding the ascending aorta and sternotomy incision, respectively. Adipose tissues were collected from patients undergoing myocardial revascularization or mitral valve replacement surgery. Morphological studies with hematoxylin/eosin and immunohistochemical assay were performed in situ to quantify adipokine expression. To analyze adipogenic capacity, adipokine expression, and the levels of thermogenic proteins, adipocyte precursor cells were isolated from periaortic and subcutaneous adipose tissues and induced to differentiation. The precursors of adipocytes from the periaortic tissue accumulated less triglycerides than those from the subcutaneous tissue after differentiation and were smaller than those from subcutaneous adipose tissue. The levels of proteins involved in thermogenesis and energy expenditure increased significantly in periaortic adipose tissue. Additionally, the expression levels of adipokines that affect carbohydrate metabolism, such as FGF21, increased significantly in mature adipocytes induced from periaortic adipose tissue. These results demonstrate that precursors of periaortic adipose tissue in humans may affect cardiovascular events and might serve as a target for preventing vascular diseases.